Exogenous glutathione supplementation in culture medium improves the bovine embryo development after in vitro fertilization - Sun, Wei-Jun; Pang, Yun-Wei; Liu, Yan; Hao, Hai-Sheng; Zhao, Xue-Ming; Qin, Tong; Zhu, Hua-Bin; Du, Wei-Hua (Theriogenology, 2015)
To determine the beneficial effects and mechanisms of exogenous glutathione (GSH) during IVC on the embryonic development, bovine IVF zygotes were cultured in medium containing different concentrations of GSH, and the rate of cleavage and blastocyst development, total cell number of blastocysts, the inner cell mass:total cell number ratio, and intracellular GSH and reactive oxygen species concentrations were investigated. Gene expressions associated with embryonic development and GSH metabolism were measured using quantitative real-time polymerase chain reaction. At the concentrations of 1, 3, and 5 mM, GSH significantly increased the blastocyst rate and embryo quality. The highest blastocyst rate (51%) and the best embryo quality appeared in the 3-mM GSH treatment. Intracellular content of GSH of embryos at the two- to four-cell stage significantly increased, and the reactive oxygen species level decreased accordingly with 3-mM GSH treatment, but no significant differences were found in the four- to eight-cell stage and blastocysts. Gene expression analysis of the embryo regulator genes (OCT4, SOX2, and KLF4), GSH synthesis genes (GCLM, GCLC, and GSS), and GSH utilization genes (GSTP, GSTM, and GPX) showed that the GSH had no significant impact on these genes. In conclusion, exogenous GSH during IVC improved developmental potential and quality of bovine IVF embryos, which was probably caused by the ability of GSH to maintain the redox balance.